UPAYA MENURUNKAN DEFECT PER UNIT DENGAN MENERAPKAN QUALITY INFORMATION SYSTEM MENGGUNAKAN METODE GUGUS KENDALI MUTU DI ASSY PLANT DEPARTEMEN PAINTING-2 - Laksono, Dondon Try (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
Industrial company, especially automotive companies posses unique characteristics compared with other companies. One of these unique characteristics are that they must own a production system which is able to meet customer requests, who recently becomes more and more interested in paint quality. Companies compete to find defect as early as possible in their production area. Painting quality parameter can be measured in number of defects found by Quality Inspection in the Vehicle Inspection line. These defects can be monitored by applying Quality Information System. This system enables faster exchange of defect information to each production operator who made mistakes thereby not reaching quality standards. Company has to invest for this system, and the investment value can be evaluated in efficiency which can also be used to raise company efficiency.